Role Of Venture Capital In Transitioning To A Knowledge Based Economy - Peaw, Lim Hun (2003)
To recognize the role and importance of venture capital in the MSC region, this survey based research was conducted involving venture capitalists based in Kuala Lumpur - Klang Village areas. The study aspires to discover the roles of venture capital in th